Pianista – obraz getta w filmowym języku Romana Polańskiego - Śliwińska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
The Pianist – the image of a ghetto in the film language of Roman Polanski The work of Roman Polański has always been a unique example of both craftsmanship and interesting subjects. Each of his films (even of those crushed by the superficial interpretations of the reviewers) functioned perfectly well in popular culture and as an artistic accomplishment. It reconciled the tastes of both sophisticated viewers and those who looked for simple entertainment. Roman Polański’s method of creation entails the use of a number of curtains (genres, popular culture subjects, popular patterns) which cover the deeply hidden truth about the world and relations among people. In The Pianist the subject of the Holocaust was used as the key to show the mechanisms that rule the world. Also in this case the most obvious diagnosis proves to be the least important. The Pianist is not an autobiography dealing with the memories from a getto. Definitely more significant is the attempt to juxtapose the image of a ghetto and its inhabitants with the film language of Roman Polański. It makes it possible to read the problem of the Holocaust against the motifs always present in his work, including the context of the cinema of the kind. In The Pianist Polański joins the precision of a craftsman with the memory of a witness. As a result, using the solutions known from Hollywood films, he tells the story of a ghetto, which is seen as the metapher of the whole world.